The Impact of Indonesian Language Teaching Material Development on Student Learning Outcomes: A Meta-Analysis - Kadek Wirahyuni; Ida Bagus Putrayasa; Made Sutama; Wayan Rasna; Nengah Martha; Nyoman Yasa (Universitas Pendidikan Ganesha, 2025)
The Indonesian Language course plays a strategic role in developing students’ critical thinking, academic writing, and scholarly communication skills. However, empirical findings on the effectiveness of Indonesian language instructional materials remain mixed and inconsistent. This study aims to synthesize empirical evidence on the effects of instructional material development on students’ learning outcomes, estimate effect sizes, and identify study characteristics influencing its effectiveness. The subjects of this study consist of 22 empirical studies conducted at higher education institutions in Indonesia and published during the 2015–2024 period. This study employs a quantitative approach using a meta-analysis method. Data were collected through a systematic literature search, study selection, and data extraction from relevant journal articles and research reports. Data analysis techniques include effect size calculation using Hedges’ g, heterogeneity testing with Cochran’s Q and the I² statistic, selection of a random-effects model, moderator analysis, and publication bias testing using funnel plots, Egger’s test, and Begg’s test. The results of the meta-analysis indicate that the development of Indonesian language teaching materials has a positive and significant effect on student learning outcomes, with a moderate-to-large effect size. Digital teaching materials, particularly e-modules, show higher effectiveness compared to printed teaching materials, and the impact of teaching material development is strongest in the cognitive learning outcome domain. These findings imply the importance of developing innovative, technology-based Indonesian language teaching materials that are integrated with active pedagogical approaches as a strategy to improve learning quality and graduate competence in higher education.